Genetics of SOS mutagenesis. - Ennis, Don Gregory. (The University of Arizona., 1988)
Previous genetic evidence suggested that RecA was required in SOS mutagenesis for its regulatory role and perhaps some other nonregulatory role (Mount, 1977; Blanco et al., 1982). I undertook a genetic study which confirmed the above studies and provided further evidence that RecA protein appeared to have a dual "role in mutagenesis; first, the cleavage of LexA repressor for the derepression of specific SOS genes and second, one or more additional role(s). For these studies a new phage mutagenesis assay was developed which allows rapid scoring of SOS mutagenesis in a large number of host mutants. I next conducted a genetic analysis to determine if the newly defined RecA mutagenesis function was separable by mutation from the numerous other phenotypes which are known to be influenced by RecA protein. From the study of recA mutants it appears that the RecA mutagenesis function(s) is genetically separable from the following RecA phenotypes: LexA cleavage, lambda cI repressor cleavage, UV resistance and homologous recombination. In addition, I discovered that the LexA cleavage function and lambda cI cleavage function is also separable. I also studied in some detail the novel genetic properties that I uncovered for recA432 mutant strains. recA432 was defined as a mutagenesis defective allele (Kato and Shinoura, 1977). LexA cleavage in recA432 cells was more easily induced that in recA⁺ cells, causing lethal filamentation of these mutant cells even at very low UV doses. I concluded that the basis for the Mut⁻ phenotype was this strain's propensity to lethally filament, which complicated the detection of mutant cells. In another set of experiments, I examined the regulatory requirements for SOS mutagenesis and Weigle phage-reactivation; I wanted to determine which SOS operons must be derepressed for this process. lexA(Ind⁻) mutant cells are defective in mutagenesis because they cannot derepress specific SOS genes required in this process. I found that the selective derepression of umuDC was sufficient to restore mutagenesis to these lexA(Ind⁻) mutants; however, derepression of umuDC and recA was required for phage reactivation.